Implementation of creative drama activities in three selected preschools / Ervina Liasoi Lumandan - Ervina Liasoi, Lumandan (2018)
There is an ongoing talk regarding the importance of implementation of creative drama activities in school during the early childhood years. Creative drama activities are to be said connected to the childï¿½s development. Childï¿½s development here include social and emotion, language, and cognitive development. The objectives of this study is too identify the type of creative drama activities done in three preschools that will relate to childï¿½s development. This study also will identify the teaching methods used by teachers in class and at the same time look into the challenges faced by teachers in teaching creative drama activities. Besides that, this study also will look into the level of teacherï¿½s understanding in teaching creative drama as well as the readiness of the teachers and the preschool in teaching creative drama. The method to measure all the objectives are through observations and interview. While we do see from the results that creative drama activities does imply on the children development, we also see that teacherï¿½s past experiences as well as background are closely connected to the delivery of the lesson. To support the teaching of creative drama activities, other factors such as conducive environment of the centre and ample materials and space does help in deliverance of creative drama activities. Through the analysis, it is suggested that preschools continue on implementing creative drama activities in class but it will also help if the centre can support teachers in understanding the activities by giving them the necessary knowledge of creative drama activities, especially for teachers that don't have the background of it. With the combination of that, it will definitely boost the learning and understanding of children in classroom as well as preparing them with the development needed for them to grow into a healthy community.